ANALISIS PROSES BERPIKIR KRITIS SISWA KELAS III DALAM MENYELESAIKAN SOAL CERITA PERKALIAN - Andi Satriya; Wahyu Herdiyanto; Jubaedah; Ilham Wibisono; Emia Priska; Seruni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the critical thinking process of third-grade students at Trisula Perwari 2 Cikini in solving multiplication story problems. The study used a qualitative approach with a case study method. The research subjects consisted of two high-achieving students and three students with learning difficulties who were selected using a purposive sampling technique. Data were collected through tests, interviews, observations, and documentation. The results showed that high-achieving students were able to fulfill critical thinking indicators in the form of interpretation, analysis, evaluation, inference, and explanation. In contrast, students with learning difficulties still experienced obstacles in understanding information, determining solution strategies, and evaluating answers. Based on the results of the study, it is known that students' mathematical conceptual abilities are still relatively low. The percentages for each indicator are: 1) Basic understanding obtained 82.14%, 2) Expressing a concept obtained 42.14%, 3) Explaining and detailing a concept or formula obtained 44.29%. Therefore, it can be concluded that most students still do not fully understand the concept of HOTS multiplication problems.